The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/0363546514557239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Distal Ulnar Collateral Ligament Tear Pattern on Contact Forces and Valgus Stability in the Posteromedial Compartment of the Elbow

Abstract: The findings suggest that surgical reconstruction should aim to reestablish at least the proximal 50% of the UCL ulnar footprint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…In these scenarios, the presence of periligamentous edema is a useful secondary sign of the presence of a tear. Within the spectrum of partial tears, those of the proximal attachment have a more significant impact on posteromedial elbow biomechanics (21,23).…”
Section: Ulnar Collateral Ligamentmentioning
confidence: 99%
“…In these scenarios, the presence of periligamentous edema is a useful secondary sign of the presence of a tear. Within the spectrum of partial tears, those of the proximal attachment have a more significant impact on posteromedial elbow biomechanics (21,23).…”
Section: Ulnar Collateral Ligamentmentioning
confidence: 99%
“…Previous studies demonstrated that the anterior bundle of the MCL (AMCL) was the primary restraint to valgus stress ( Morrey and An, 1983 ; Hassan et al, 2015 ; Frangiamore et al, 2017 ), the posterior bundle of the MCL (PMCL) could resist motion of the humero-ulnar joint ( Shukla et al, 2016 ), and the transverse bundle of the MCL had little effect on maintaining medial stability ( Morrey and An, 1983 ). Based on the importance of AMCL, many alternative reconstruction techniques for the role of AMCL had been proposed ( Rohrbough et al, 2002 ; Paletta and Wright, 2006 ; Schwartz et al, 2008 ; Cain et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Elbow joint contact patterns have been considered to reflect pathological conditions such as UCL tears 7 . Based on this theory, Bey et al reported that joint contact patterns are not only a more sensitive measurement than conventional kinematics for detecting subtle differences in joint function but they may also provide a more clinically relevant indication of the extent to which a conservative approach or a surgical procedure has adequately restored normal joint function 8 .…”
Section: Introductionmentioning
confidence: 99%